Exploring the Distinct Characteristic of Two Procedures for Sulcus Implementation following Posterior Capsular Rupture during Phacoemulsification: Single-piece Foldable IOLs and Polymethylmethacrylate IOLs: Poster Presentation - Case Report - Ophthalmologist - Pramono, Barii Hafidh; Sophian, Darmawan M. (Majalah Oftalmologi Indonesia, 2023)
Introduction : Posterior capsular rupture (PCR) is one of the most feared complications of phacoemulsification. In? the?bag implantation of the lens becomes difficult if the PCR was large. Implantation of rigid polymethylmethacrylate (PMMA) or single?piece foldable IOL is implanted in the sulcus Case Illustration : After noting the PCR on both patients, single?piece foldable IOL of the same power was implanted in the ciliary sulcus. Same action was implemented to PMMA IOLs by enlarging the main port twice. Intracameral pilocarpine was injected and vitrectomy anterior was performed. The wound was closed with hydration on single-piece foldable IOL, meanwhile on PMMA IOLs, one hecting is required in the middle of mainport wound. The postoperative VA on day 1 from 0.12 on single-piece foldable IOLs and 0.25 on PMMA IOLs. Corneal edema, increased anterior chamber reaction was seen on single-piece foldable IOLs. Raised IOP was not found on both patients Discussion : Complications implantation single?piece foldable IOLs such as pigment dispersion syndrome, increased IOP. A surgical peripheral iridectomy can be created as a solution. Complication less likely occurred on the patient with longer axial length. The AL on this patient is AL 23.33 mm (single?piece foldable IOLs) and 24.08 mm (PMMA IOLs). The weakness of single piece foldable acrylic lenses are poor choice for ciliary sulcus placement and PMMA IOLs can induce astigmatism. Conclusion : Single-piece foldable IOLs are not designed for sulcus implantation. PMMA IOLs implantation can induce astigmatism.